Metabolic, humoral and haemodynamic characteristics of normotensive offspring from hypertensive families - Horký, K; Jáchymová, M; Jindra, A; Savliková, J; Peleska, J; Umnerová, V; Linhart, A (Journal of human hypertension, 1996)
Arterial hypertension is not only a haemodynamic abnormality, but it is associated with several metabolic and humoral changes. Heredity appears to be participating in the pathogenesis of essential hypertension (EH). We studied whether some metabolic, humoral and haemodynamic changes could be detected in genetically predisposed normotensive sons of hypertensive families (SH) compared with normotensive sons of normotensive parents (SN). The study groups consisted of 40 young SN and 40 SH matched for age and body mass index (BMI). Blood samples for laboratory determination were taken under basal conditions and 90 min after a 75 g glucose load. SH already had a higher systolic blood pressure (BP) (120.7 +/- 1.7 mm Hg) and a tendency to a higher diastolic BP than the SN group. In spite of the fact that both basal and stimulated glycemia did not differ significantly between the study groups, significantly higher glucose-stimulated immuno-reactive-insulin (IRI) was found in SH (80.1 +/- 7.06 vs 62.9 +/- 5.76 uU/l). Higher plasma concentration of catecholamines in SH indicate their higher sympathetico-adrenal activity. The groups did not differ significantly in basal and stimulated plasma renin activity (PRA), aldosterone and atrial natriuretic peptide (ANP). There was a tendency for higher levels of endothelin (ET) in the plasma of SH. The glucose load increased as expected, glycemia, IRI and C-peptide, but ANP and ET concentrations were unexpectedly reduced. These abnormalities were associated, in SH, with higher left ventricle (LV) mass index and impaired diastolic filling. Persistence of high LV mass index, even after adjustment for respective systolic BP, suggests the participation of more than haemodynamic stress in the increase of LV mass. Our results suggest that in normotensive genetically predisposed subjects from hypertensive families, some metabolic and humoral abnormalities can already be detected. They might be responsible for the higher BP readings with subsequent manifestations of hypertension and LV morphological and functional abnormalities.
Keywords: Blood Pressure; Hypertension; Hemodynamics; Hormones; Adult; hormony; Male; hypertenze; Reference Values; dospělí; hemodynamika; krevní tlak; lidé; mužské pohlaví; Echocardiography; referenční hodnoty; Humans; echokardiografie